2023
DOI: 10.3390/foods12183456
|View full text |Cite
|
Sign up to set email alerts
|

UHPLC-ESI-QTOF-MS/MS Profiling of Phytochemicals from Araticum Fruit (Annona crassiflora Mart.) and Its Antioxidant Activity

Henrique Silvano Arruda,
Célio Fernando Figueiredo Angolini,
Marcos Nogueira Eberlin
et al.

Abstract: Araticum is a native species of the Brazilian Cerrado with a high potential for exploitation. Several studies have stated that araticum is a rich source of phytochemicals with multifaceted biological actions. However, little information is available regarding the characterization of phytochemicals found in the pulp of this fruit. In this context, this study aimed to carry out a comprehensive characterization of phytochemicals present in the araticum pulp using ultra-high-performance liquid chromatography coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 103 publications
(131 reference statements)
0
1
0
Order By: Relevance
“…Among these, 2-isopropylmalic acid ( 43 ) and 3-hydroxy-3-(methoxycarbonyl)pentanedioic acid ( 25 ) were previously reported to have promising antioxidant activities. 68–70 In another study, dicrotalic acid ( 35 ) was found to be more evident in a fraction of Prunus cerasifera L. which showed a greater antioxidant activity in DPPH and ABTS assays. 71 Additionally, extracts rich in jasmonic compounds such as sulfo jasmonate were found to have significant anticancer, anti-inflammatory, and cosmetic properties.…”
Section: Resultsmentioning
confidence: 93%
“…Among these, 2-isopropylmalic acid ( 43 ) and 3-hydroxy-3-(methoxycarbonyl)pentanedioic acid ( 25 ) were previously reported to have promising antioxidant activities. 68–70 In another study, dicrotalic acid ( 35 ) was found to be more evident in a fraction of Prunus cerasifera L. which showed a greater antioxidant activity in DPPH and ABTS assays. 71 Additionally, extracts rich in jasmonic compounds such as sulfo jasmonate were found to have significant anticancer, anti-inflammatory, and cosmetic properties.…”
Section: Resultsmentioning
confidence: 93%